2021
DOI: 10.1101/2021.04.16.439894
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A content-based representational scaffold for naturalistic event memories

Abstract: Real-world events are complex, featuring elements that may be unique to, or shared across, multiple situations. In the present study, we used fMRI to identify how different event components are represented in real-time and during memory retrieval. Twenty participants viewed and recalled eight videos depicting real-world events, combining people, contexts, and context types. Multi-voxel pattern similarity analyses revealed specific person representations, persistent across contexts, in regions of an Anterior-Te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 123 publications
(249 reference statements)
2
8
1
Order By: Relevance
“…Given the strong involvement of mPFC during schematic encoding, it has been hypothesized that mPFC may play a role at retrieval by providing schematic cues for memory search (van Kesteren et al, 2012). While some studies have found that schema-related activity in mPFC during retrieval benefits memory (Brod et al, 2015;van Kesteren et al, 2010b;Müller et al, 2020;Webb and Dennis, 2019;Raykov et al, 2021), others have not (van Buuren et al, 2014;Webb et al, 2016;Guo and Yang, 2020;van der Linden et al, 2017;Reagh et al, 2021). In our study, we did not observe strong mPFC schema reinstatement, nor were able to relate it to a behavioral memory benefit.…”
Section: Relationship Between Schematic Representations During Retrieval and Memory Performancecontrasting
confidence: 67%
See 3 more Smart Citations
“…Given the strong involvement of mPFC during schematic encoding, it has been hypothesized that mPFC may play a role at retrieval by providing schematic cues for memory search (van Kesteren et al, 2012). While some studies have found that schema-related activity in mPFC during retrieval benefits memory (Brod et al, 2015;van Kesteren et al, 2010b;Müller et al, 2020;Webb and Dennis, 2019;Raykov et al, 2021), others have not (van Buuren et al, 2014;Webb et al, 2016;Guo and Yang, 2020;van der Linden et al, 2017;Reagh et al, 2021). In our study, we did not observe strong mPFC schema reinstatement, nor were able to relate it to a behavioral memory benefit.…”
Section: Relationship Between Schematic Representations During Retrieval and Memory Performancecontrasting
confidence: 67%
“…Because mPFC has been frequently implicated in previous schema research (e.g., van Kesteren et al, 2010a(e.g., van Kesteren et al, , 2013(e.g., van Kesteren et al, , 2014(e.g., van Kesteren et al, , 2020Baldassano et al, 2018;Raykov et al, 2020Raykov et al, , 2021Reagh et al, 2021) -in particular with regard to integrating new knowledge into existing schemas (Preston and Eichenbaum, 2013;Gilboa and Marlatte, 2017;Tse et al, 2007;Wang and Morris, 2010;van Kesteren et al, 2012) -we predicted that robust mPFC schema representations at encoding would lead to improved subsequent memory for the narrative. Based on prior work implicating the hippocampus in schema representation (van Kesteren et al, 2013(van Kesteren et al, , 2014(van Kesteren et al, , 2020Brod et al, 2015;Liu et al, 2017;Raykov et al, 2020;Webb et al, 2016;van der Linden et al, 2017;Bonasia et al, 2018), we also hypothesized that hippocampal schema representations at encoding would support subsequent memory; more specifically, based on work showing that hippocampus has a coarse-to-fine gradient of representations along its long axis (Collin et al, 2015;Guo and Yang, 2020;Audrain and McAndrews, 2020;Poppenk et al, 2013;Brunec et al, 2018;Sekeres et al, 2018), we predicted that anterior hippocampus (which has coarser and thus more general representations than posterior hippocampus) would contain schematic representations that contribute to subsequent memory, whereas posterior hippocampus would contribute to subsequent memory by representing story-specific details.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…It is also possible to generate testable hypotheses about many other brain areas that might be involved in this task. For completeness, we have included post hoc analyses (see STAR Methods) that test for narrative coherence effects, within two key cortical networks Article that interact with the hippocampus [52][53][54][55] : the posterior medial (PM) network, which supports information about event contexts (e.g., types of situations); and the anterior temporal (AT) network, which supports information about particular entities within events (e.g., people or objects). Because stories were presented aurally, we also investigated auditory cortex.…”
Section: Post Hoc Analyses Of Cortical Networkmentioning
confidence: 99%